INVESTIGASI VARIABEL PENENTU PENGELOLAAN KEUANGAN UMKM DI YOGYAKARTA: LITERASI KEUANGAN, SIKAP DAN PENDAPATAN - Rahmawati Yusrianthe; Budi Asmarawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research aims to explore the influence of financial literacy, financial attitudes and income on financial management in Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta. The samples in this research were MSME actors in the Yogyakarta area and its surroundings. The data analysis techniques used include descriptive statistics, validity testing, reliability testing, classical assumption testing and hypothesis testing using multiple linear regression. The research results show that financial literacy and income have no influence on financial management of MSMEs in Yogyakarta, while financial attitudes show no influence on financial management of MSMEs in Yogyakarta. Suggestions for the Yogyakarta City government, through the Department of MSMEs, Industry and Trade, continue to make efforts to increase financial literacy for MSME owners in the Yogyakarta City area by conducting seminars or training/workshops related to insight into finance and good financial management in the hope of increasing their abilities and financial insights that MSME owners.